Efisiensi Ekonomi Postner dan Kritik Terhadap Keadilan Sosial - Amrizal Siagian; Achmad Muchtarom; Ario Karyono; Biem Triani Benjamin; Faisal Santiago (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The dominance of the law and economics approach, championed by Richard A. Posner, promotes wealth maximization and economic efficiency as the paramount objectives of law. This creates a fundamental gap with distributive justice theories, which posit that the law's primary ethical duty is to ensure equity and moral fairness. The central problem is the apparent tension between a legal system designed for optimal resource allocation and one obligated to deliver social justice, raising critical questions about law's normative foundations. This dialectic is especially significant for pluralistic jurisdictions like Indonesia, where legal ideals must reconcile with socio-cultural values. This study employs qualitative method with a normative-philosophical research design, conducting a critical analysis of primary texts from Posner, Rawls, Sen, and Dworkin. The analytical method involves philosophical argumentation and comparative legal theory to deconstruct the premises and implications of both paradigms. The analysis reveals that while economic efficiency offers a valuable practical framework for predicting behavioral incentives and evaluating legal outcomes, it operates within an amoral calculus that fails to address fundamental questions of rights, dignity, and equitable distribution. As a result, efficiency cannot support social justice as the ethical cornerstone of law. For Indonesia, this necessitates a constitutional synthesis where efficiency-based instruments are consciously subordinated to and harmonized with the principles of Pancasila and the 1945 Constitution, which enshrine social justice. Therefore, it is recommended that Indonesian legal scholarship and policymaking explicitly adopt an integrated framework where efficiency serves as a tool within, not the goal of, a justice-oriented legal system.